Digital Labour Market Model and Financial Opportunities in the Context of Sustainable Development in the EU Countries - Ciobanu, Ghenadie; Dinu, Mihai; Iacob (Pârgaru), Oana Camelia; Constantinescu, Victor George (European Journal of Sustainable Development, 2022)
Technological opportunities have a transformative impact on labour markets. In this article, we aim to study the ways in which digital technologies contribute to the development of the digital model of the labour market and digital platforms. We aim to highlight digital opportunities to support efforts to ensure the development of strategies, policies and labour market transformations. We intend to build the digital model of the labour market within the model of the systemic digital economy, in close connection with other digitalization models (business, financial markets, public finance, commerce, industry, agriculture, transport). An important part of the study focuses on the opportunities for sustainable financing of the digitized labour market, as financial services interact closely with labour market institutions, which reflect on labour outcomes. We propose that the digital model of the labour market in close correlation with the digital business model will developed with investments from employers in the training of employees in digitization, new modern professional knowledge, which will allow an integration of companies in global markets. The financial-monetary dimension of companies in the context of globalization also requires radical transformations to ensure companies' access to the international financial markets.